Comprehensive Methodological Approach to Determining Lipids in Clams - Alexandra V. Borodina; Yurii O. Veliaev; Alexander R. Osokin (Техника и технология пищевых производств)
Marine bivalves are rich in polyunsaturated fatty acids. Cerastoderma glaucum is a potentially commercial sea cockle that inhabits the Mediterranean and the Black Seas. This bivalve mollusk contains omega-3, omega-6, and omega-9 fatty acids. However, its lipid composition remains understudied. When determining total lipids, their classes, and fatty acid composition, standard methods often have to be adapted to the object in hand and tools available. The research objective was to develop a complex lipid analysis method for aquatic organisms. The study featured total soft tissues of C. glaucum harvested from the pseudolittoral zone on the sand and silt soil of the Sevastopol coast of the Black Sea. The chromatographic methods made it possible to identify total lipids and classify them into phospholipids, monoglycerides, diglycerides, sterols, and triacylglycerols. The subsequent densimetric determination involved a flatbed scanner and the TLC Manager 4.0.2.3D software. The fatty acid composition for total lipids was studied using the chromatography-mass spectrometric method. The existing methods in lipidology were adapted for determining total lipids, their classes, and the fatty acid composition of total lipids in C. glaucum. The article introduces a detailed description of the method for determining total lipids, as well as of how to prepare equipment and reagents to classify common lipids using multidimensional thin layer chromatography. It also contains an authentic scheme of chromatographic baths for stepwise separation, densitometric measurements, and examples of fatty acid chromatograms and mass spectra. The new sample preparation method for determining fatty acids in total lipids by gas chromatography demonstrated a minimal loss in native structure and proved to be less aggressive than standard methods of sample derivatization. The new method for lipid analysis of clam tissues appeared to be economical, less time-consuming, and reagent-intensive. It can be recommended for small laboratories engaged in bioenergetics or comparative analyzes of aquatic organisms.